IMPROVING STUDENTS' CREATIVE ACTIVITY THROUGH ART PEDAGOGY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the improvement of students' creative activity through digital technologies, the current state of the digitalization process, existing technologies, their impact on the educational process and the possibilities of their application. Also, the advantages and problems of digital tools in primary education lessons are highlighted. In the scientific work, current issues in the field and ways to solve them are also considered.